2000
DOI: 10.1006/jmsc.1999.0523
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment in flatfish, with special emphasis on North Atlantic species: Progress made by the Flatfish Symposia

Abstract: In summarizing the main results on recruitment that emerged from the series of Flatfish Symposia, two aspects were distinguished: mean level and interannual variability. Recruitment to a stock appears to be related to the quantity of juvenile nursery habitats, suggesting that either larval supply or the carrying capacity of the nurseries is the limiting factor. However, available information on growth of 0-group flatfish suggests that the carrying capacity of nursery areas is never reached. Variability in year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
127
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(130 citation statements)
references
References 79 publications
(120 reference statements)
3
127
0
Order By: Relevance
“…Survival and growth of early fish stages are maximised in these highly productive habitats (Miller et al 1984(Miller et al , 1988 and natural shallow areas can serve as nurseries for a variety of species that are widely distributed on the continental shelf (Lenanton & Potter 1987), in particular flatfishes (Van der Veer et al 2000, Riou et al 2001. The available area and the quality of coastal nursery habitats have a considerable influence on recruitment levels (Rijnsdorp et al 1992, Gibson 1994 and damage to these habitats may slow or prevent population recoveries (Hall 1998, Hill & Caswell 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Survival and growth of early fish stages are maximised in these highly productive habitats (Miller et al 1984(Miller et al , 1988 and natural shallow areas can serve as nurseries for a variety of species that are widely distributed on the continental shelf (Lenanton & Potter 1987), in particular flatfishes (Van der Veer et al 2000, Riou et al 2001. The available area and the quality of coastal nursery habitats have a considerable influence on recruitment levels (Rijnsdorp et al 1992, Gibson 1994 and damage to these habitats may slow or prevent population recoveries (Hall 1998, Hill & Caswell 2001.…”
Section: Introductionmentioning
confidence: 99%
“…By meta-analysis, Rijnsdorp et al (1992) found a positive relationship between average recruitment success and spatial extension of the nursery grounds for sole, which holds also for different plaice populations around the North Sea ( Van der Veer et al, 2000). Similar to flatfish, density dependent mortality has been detected in walleye pollock during the transition between the larval and the juvenile phase (Bailey et al, 1996).…”
Section: Density Dependence In the Juvenile Stagementioning
confidence: 94%
“…Density dependent mortality has been identified in different flatfish species during the phase shortly after settlement, dampening the inter-annual variability in recruitment, but not explaining a significant part of the variability ( Van der Veer et al, 2000).…”
Section: Density Dependence In the Juvenile Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Such habitats are generally highly productive, providing abundant food resources as well as protection to early juveniles against predators, features which allow fish to optimize the trade-off between growth and survival (Bergman et al, 1988;Beck et al, 2001;Gibson et al, 2002). Both the capacity and quality of the nursery (Gibson, 1994;Iles & Beverton, 2000;Rijnsdorp et al, 1992;van der Veer et al, 1994van der Veer et al, , 2000 and its connectivity with the adult habitat (Beck et al, 2001;Gillanders et al, 2003) are considered to influence annual recruitment levels to adult stocks in offshore waters. The residency of juvenile fish in nursery areas is speciesdependent and can range from several weeks to multiple years (Cabral & Costa, 1999;Martinho et al, 2007;Laurel et al, 2009), and the longer the permanence, the stronger the potential influence of habitat (biotic and abiotic) factors on growth and cohort survival (see review by Gibson, 1994).…”
Section: Introductionmentioning
confidence: 99%